2014
DOI: 10.1136/archdischild-2014-307384.140
|View full text |Cite
|
Sign up to set email alerts
|

O-071 Salt-sparing Diuretic Action Of A Urea Analogue Inhibitor Of Urea Transporters Ut-a And Ut-b In Rats

Abstract: Background and aims If infants fail to initiate spontaneous breathing after birth, international guidelines recommend positive pressure ventilation (PPV). However, mask PPV remains challenging with leakage occurring commonly. Despite a variety of available facemasks, none has been systemically studied in newborn infants. We aimed to determine if using a Fisher and Paykel (FP) round facemask would reduce mask leak compared to using a Laerdal round facemask during mask PPV in preterm infants.Methods From April t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The antiserum of UT-A3 was detected at the carboxyl end of UT-A3, and it was found that UT-A3 existed in the cell armament of IMCD. It can be used as a cell's UTS storage tank, and has the ability to enter the plasma membrane, leading to the rapid improvement of urinary system permeability [9].…”
Section: Urea Channel Proteinmentioning
confidence: 99%
“…The antiserum of UT-A3 was detected at the carboxyl end of UT-A3, and it was found that UT-A3 existed in the cell armament of IMCD. It can be used as a cell's UTS storage tank, and has the ability to enter the plasma membrane, leading to the rapid improvement of urinary system permeability [9].…”
Section: Urea Channel Proteinmentioning
confidence: 99%